Antibiotic stewardship: Why we must, how we can - SRINIVASAN, ARJUN (Cleve Clin J Med, 2017)
Improving our antibiotic use is critical to the safety of our patients and the future of medicine. This can improve patient outcomes, save money, reduce resistance, and help prevent negative consequences such as Clostridium difficile infection. The US Centers for Disease Control and Prevention (CDC) is undertaking a nationwide effort to appropriately improve antibiotic use in inpatient and outpatient settings.